Women's Position And Role In Charlotte Bronte's Shirley:A Feminist Approach - Murdianti, Listio (2004)
The object of the research is the novel entitled Shirley by Charlotte Bronte. The study gives focus on the women's position and role as reflected in Charlotte Bronte's Shirley. The aim of the study is finding the women's position and role. The analysis uses descriptive qualitative by describing the structural elements and feminist analysis. The approach uses feminist theory. The primary source of criticism toward the novel is used for further analysis. The data collecting technique is library research. The data analysis uses descriptive technique and content analysis. The outcome of the study is, Shirley is Bronte's work that represents the social criticism, a protest against both insentivity of the mill owners and the subservient position of women. Bronte does not agree with the condition in English culture. She wants to change the opinion of the people. The result of the feminist analysis shows that Bronte insists that women's position and role should be equal to those of men.